2007
DOI: 10.1001/archinte.167.11.1166
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prescription in Palliative Sedation

Abstract: Background: Two guidelines addressing palliative sedation have been published in the Netherlands in 2002 and 2003. The objective of the present study is to determine adherence to the guidelines for palliative sedation with regard to prescription. The study is restricted to the practice of continuous deep palliative sedation. Methods: A structured retrospective questionnaire was administered to 1464 physicians concerning their last case of deep sedation during the past 12 months. Physicians included Dutch hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 22 publications
4
32
1
Order By: Relevance
“…A previous Dutch study suggested that the choice of drugs for continuous deep sedation is associated with the use of guidelines and being a palliative expert or consultation of a palliative care expert. 10 Our study confirmed the relation between consultation and adequate drug use. Such consultation, however, occurred in only a small number of the cases in our study, maybe because most of the physicians consider the application of continuous deep sedation as normal medical practice that is part of their own expertise or because they were not well informed about it or did not have access to palliative consultation.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 83%
See 1 more Smart Citation
“…A previous Dutch study suggested that the choice of drugs for continuous deep sedation is associated with the use of guidelines and being a palliative expert or consultation of a palliative care expert. 10 Our study confirmed the relation between consultation and adequate drug use. Such consultation, however, occurred in only a small number of the cases in our study, maybe because most of the physicians consider the application of continuous deep sedation as normal medical practice that is part of their own expertise or because they were not well informed about it or did not have access to palliative consultation.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 83%
“…An important aspect of the debate concern the conditions under which this practice is medically indicated [3][4][5][6][7][8] and the way it is performed. [8][9][10][11] On the basis of their expertise and an extensive literature review, an expert group recently recommended that to warrant sedation at the end of life, the patient's condition should be irreversible and advanced, with death expected within at most one to two weeks. 8 Further recommendations were that benzodiazepines should be the drug of first choice, that hydration should be offered to sedated patients only when the benefit will outweigh the harm, and that advice from palliative care specialists should be sought before sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines should specify the nursing responsibilities according to their various roles (e.g., specialist palliative care nurse versus generalist) (95). Further research evaluating the effectiveness and adherence to CPGs is required (96,97).…”
mentioning
confidence: 99%
“…[6][7][8] An important reason for continuous deep sedation being thought of as controversial is the possible association of this practice with the hastening of death, [9][10][11] although it is also argued that palliative sedation does not shorten life when its use is restricted to the patient's last days of life. 12,13 Guidelines for palliative sedation often advise physicians to titrate sedatives, 2,3,14 which means that the dosages of sedatives are adjusted to the level needed for proper relief of symptoms. To date, research has predominantly focused on the indications and type of medications used for sedation.…”
mentioning
confidence: 99%